Preventing Foodborne Illness: Norovirus - Keith R. Schneider; Renée M. Goodrich; Michael J. Mahovic; Rajya Shukla (EDIS)
"Norovirus" was recently designated as the official genus name for the group of viruses previously described as “Norwalk-like viruses” (NLV). Noroviruses (family Caliciviridae, genus Norovirus) are a group of non-enveloped, single-stranded RNA viruses found worldwide, with humans being the only known host. Norovirus, similar to Norwalk virus, causes an illness called gastroenteritis, which is commonly referred to as “the stomach flu” (no relation to the common flu, which is a respiratory illness caused by the influenza virus).  This document is FSHN05-18, one of a series of the Food Science and Human Nutrition Department, UF/IFAS Extension. Original publication date October 2005.